2021
DOI: 10.20960/nh.03848
|View full text |Cite
|
Sign up to set email alerts
|

Does fetuin-A mediate the association between pro-inflammatory diet and T2DM risk?

Abstract: Introduction: recent studies indicate that diet increases T2DM risk via inflammation. Fetuin-A, identified as an acute-phase protein, plays a role in insulin resistance and is an independent predictor of type-2 diabetes. Objectives: the present study aimed to examine the association between diet and T2DM risk, and whether said association is mediated by fetuin-A, and to determine the effect of fetuin-A on T2DM risk. Methods: the case group included 40 individuals with T2DM, whereas 40 individuals without T2DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“… 93 In addition, a previous study suggested that a pro-inflammatory diet might aide IR and T2D development via fetuin-A. 94 Moreover, a thorough meta-analysis comprising more than 110 00 participants concluded that increased circulating levels of fetuin-A were linked to an elevated risk of T2D. 95 Serum fetuin-A levels have been proposed to be used as a potential biomarker regarding IR and PCOS.…”
Section: Insulin Resistancementioning
confidence: 99%
“… 93 In addition, a previous study suggested that a pro-inflammatory diet might aide IR and T2D development via fetuin-A. 94 Moreover, a thorough meta-analysis comprising more than 110 00 participants concluded that increased circulating levels of fetuin-A were linked to an elevated risk of T2D. 95 Serum fetuin-A levels have been proposed to be used as a potential biomarker regarding IR and PCOS.…”
Section: Insulin Resistancementioning
confidence: 99%
“…No grupo controle, além de ser notado as diferenças de aumento na avaliação antropométrica, também foi notado um aumento significativo nos marcadores inflamatórios como Fetuína-A, Interleucina-6 e Interferon-α, no qual demonstrou a ação da fetuína-A sob estas células pancreáticas. Neste estudo a inflamação causada pela alimentação pró-inflamatória do grupo controle causaram danos em níveis genéticos mediadas pela fetuína-A nas células beta, o que corresponde ao risco aumentado de desenvolver DM2 (Toprak et al, 2022).…”
Section: Fatores Genéticosunclassified